Pengaruh Latihan Pernapasan Metode Pursed Lips Breathing Terhadap Kualitas Hidup Pasien PPOK Stabil Di RSUD Labuang Baji Makassar - Haerul P; Muhammad Arif Mansur (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
COPD is a chronic disease where monitoring of the effectiveness of treatment is not only obtained from clinical parameters, but rather from patient perspective parameters, one of which is quality of life. Quality of life is an individual's ability to function in various desired roles in society and to feel satisfied with these roles. Some non-pharmacological therapy techniques that can be taught are inspiratory muscle exercises such as the pursed lips breathing method. This study aims to identify the effect of pursed lips breathing breathing exercises on the quality of life of patients with stable COPD. This study used a pre-experimental method with a one-group pretest posttest design. The population in this study were patients suffering from stable COPD who visited the pulmonary polyclinic of Labuang Baji Hospital. The sampling technique used consecutive sampling, with a large number of samples, namely 27 people. Data analysis in this study used paired t-test statistical test. The results showed that before the pursed lips breathing method was practiced, the average quality of life (pre) was 58,874, while the average quality of life after the pursed lips breathing (post) method was 42,863. The results of the parametric paired t test show p value = 0.000, because p value 0.000 <0.05, then Ho is rejected. Thus, it can be concluded that there is an effect of the pursed lips breathing method on the quality of life of stable COPD patients at Labuang Baji Hospital Makassar. It is recommended to health workers, especially nurses, to be able to provide non-pharmacological therapy, one of which is the pursed lips breathing method for Stable COPD patients as part of implementing collaborative nursing interventions.